Production of optical pure L-lactic acid from Cabernet Sauvignon grape pomace by engineered Lactiplantibacillus plantarum - Shen, Yuli; Kang, Bohua; Lu, Yi; Du, Xinyuan; Qin, Chuan; Li, Jing; Zhao, Zhaoer; Yu, Ran; Shi, Suan; Han, Lujia (Frontiers in Energy Research, 2023)
Cabernet Sauvignon grape pomace contains carbohydrates and various amino acids that could be used as substrates for lactic acid (LA) production. In this study, a mutant strain of L. plantarum with deletion of the D-lactate synthesis gene was developed and used to produce optical pure L-LA from grape pomace. The highest optical purity of the L-LA produced by this mutant strain was 99.61%. The direct bioconversion of the raw substrate showed a low LA yield. Several pretreatment methods were applied to improve the LA yield, including ball milling, hydrothermal, dilute acid pretreatment, alkaline pretreatment, and combined wet alkaline mechanical pretreatment. Due to the efficient delignification, alkaline pretreatment achieved the highest lactic acid yield of 96.26% at 15% solid loading, with corresponding LA concentration and volumetric productivity of 18.45 g/L and 2.30 g/L·h, respectively.